Strength and elastic properties of cassava tuber - Kolawole, O.P.; Agbetoye, L.A.S.; Ogunlowo, A.S. (2007)
In this study, some engineering properties of cassava tuber samples were determined experimentally under five moisture content levels of 70 %, 65 %, 60%, 55 %, and 50 %wet basis. The properties measured were tensile strength, compressive strength and elasticity. Three experimental tools were designed and fabricated using spring balance, hose-clips, and 12Volts motor with reels and rope for the investigations. The IITA improved cassava variety TMS 4(2) 1425 was used in the experiments. Results of the tests indicated that all the properties measured were influenced by the moisture contents of the tuber.